Digital Influencer Sebagai Alternatif Baru Dalam Promosi Rintisan Desa Wisata Pada Desa Sedang Abiansemal Bali - AA. Istri Putri Dwi Jayanti; Rani Chandra Oktaviani; Jati Paras Ayu (ASIAN PUBLISHER, 2023)
This study was carried out by looking at the background of tourist villages, however there are still several villages that have tourism potential but have not received recognition from the Ministry of Tourism and Creative Economy as tourist villages. One of the villages that is of concern is the village of Sedang, Abiansemaal Badung Bali, where the village is rich in places; religious tourism, cultural tourism, and agro tourism which is rich in typical plants but on the other hand is still in the pioneering process of getting the title as a tourist village. Of the several main indicators in the verification process instrument as a tourist village, there are at least 7 aspects; there are tourist attractions, transportation routes, tourism awareness devices and groups, security, available homestays and tourist visits. Looking at the conditions in the middle village, the main problem lies in the relatively small number of tourist visits, this is due to the village's position between several other tourist villages, so that the middle village is more of a transit village than a visiting village because of its tourism potential. For this reason, this study looks at the importance of acceleration and penetration of target tourists so that they are aware and have the intention to travel to Sedang village. The community service program that has been implemented is through mapping tourist targets and implementing digital influencer innovation, where currently the use of digital influencers has become an alternative for disseminating information massively and persuasively. The aim of implementing this program is to be a tactical step to attract tourists to visit the village of Sedang through reviews, promotions and the logic of communication networks through digital media. The methods used in this program are 1) Providing Digital Influencer Innovation and assistance to village parties as shown in the Web Virtual Tour, 2) Quantitatively measuring the increase in the ability of village officials in managing digital influencers, 3) Measuring digital analytic data from responses resulting from use digital influencer integrated with a virtual web tour. Temporary activity results show that 40% of participants were able to use digital influencers and there was an increase in visit response with an increase of 10% in one month since a simulation of using digital influencers was created. It can be concluded that there are quite significant implications in the use of digital influencers, especially in the increase in the number of tourists coming, but what is important to concentrate on is selecting influencers and persuasive messages which are aspects that need to be considered in managing digital influencers